Research on Zero Voltage Ride-through Control Strategy of Photovoltaic Grid-connected Inverter - CHEN Yifeng; ZHAO Xianggui; WANG Nan; LIU Zhaoyi (Kongzhi Yu Xinxi Jishu)
Based on the adverse effects of unexpected power fall caused by grid-breakdown of photovoltaic power station. It designed a control strategy of zero voltage ride through of the photovoltaic(PV) inverter. High-speed phase-locked technology is used based on the positive sequence voltage and a certain amount of reactive power are provided by the grid-connected inverter to support the network voltage according to the drop degree of grid voltage, which makes the inverter keep grid-connected state when the instantaneous power fall occurrs. Semi-physical simulation experimental results prove the validity and reliability of the technical scheme.